Perception of local residents on the roadside trees at Jalan Iskandar, Kampar, Perak - Zulkefli, Nur Syahirah (2018)
Roadside trees often damage personal properties and sometimes take lives of people when the branches or the tree falls suddenly during storm or when the trees are infested by diseases. Most of the roadside trees are planted to beautify an area and rarely these trees are planted based on its function and uses. This research aims to identify the benefits and the problems of roadside trees from the perspective of local residents. The research was conducted involving 200 local residents residing along Jalan Iskandar, Kampar, Perak. The results showed that most of the local residents are aware of the benefits of roadside trees such as providing shade, reduce air pollution and providing pleasant and healthy view. The local residents are also aware of the problems of the roadside trees such as the potential of roadside trees damaging the pavement and the growth of fungal diseases weakening the roadside trees. Local residents do agreed that huge and mature roadside trees should be cut down.